ANALYSIS OF WASTE MANAGEMENT IN WOOD SAWING PROCESSES VIA THE PDCA CYCLE (REMUNOM, 2026)
The forestry sector is of great importance to the Brazilian GDP due to the wide range of timber products available. However, the sustainable management of its by-products, governed by the National Solid Waste Policy, still faces operational challenges. The application of the PDCA (Plan, Do, Check, Act) cycle emerges as a strategic tool to increase efficiency and competitiveness, balancing economic and environmental demands. This study analyzed the utilization and management of waste in the sawing process of a small sawmill in Murici-AL, which exclusively uses the Artocarpus heterophyllus (jackfruit) species for the manufacture of rustic furniture and jointers. The methodology consisted of applying questionnaires and in situ evaluations of qualitative and quantitative data. The results demonstrated that wood yield varies according to the dimensions of the piece received: larger pieces showed a yield of up to 75%, while smaller pieces yielded less than 50%. It was observed that square-shaped pieces are the most profitable for the company compared to rectangular ones. The main residues generated include sawdust, wood shavings, trimmings, and defective pieces. The study highlighted the absence of a Solid Waste Management Plan (PGRS) and the lack of partnerships for proper disposal, resulting in material accumulation and extra disposal costs. The PDCA tool was applied to diagnose the problems and propose corrective actions. In planning, goals were defined for waste reduction; in execution, technical sorting was suggested; in verification, systematic yield monitoring; and in action, the search for by-product markets. It is concluded that PDCA is efficient for organizing production flow, adding value to waste, and ensuring compliance with environmental legislation, transforming liabilities into market opportunities.